Development of emergent processes and threshold of consciousness with levels of processing - Watanabe, Ryoichi; Moriguchi, Yusuke (Frontiers in Psychology, 2024)
Introduction The transition of experience from unconscious to conscious, the emergent process, is a crucial topic in consciousness studies. Three frameworks exist to explain the process: (1) consciousness arises in an all-or-none manner; (2) consciousness arises gradually; (3) consciousness arises either all at once or gradually, depending on the level of stimulus processing (low- vs. high-level). However, the development of emergent processes of consciousness remains unclear. This study examines the development of emergent processes of consciousness based on the level of stimulus processing framework. Methods Ninety-nine children (5–12 year-olds) and adults participated in two online discrimination tasks. These tasks involved color discrimination as lower-level processing and number magnitude discrimination as higher-level processing, as well as backward masking with stimulus onset asynchronies (SOAs) varying from 16.7 to 266.7 ms. We measured objective discrimination accuracy and used a 4-scale Perceptual Awareness Scale (PAS) to assess subjective awareness. We fit the data to a four-parameter nonlinear function to estimate the center of the slope (threshold) and the range of the slope (gradualness, the measure of emergent process of consciousness) of the model. Results The results showed the threshold of objective discrimination was significantly higher in 5–6 year-olds than in 7–12 year-olds, but not of subjective awareness. The emergent process of objective discrimination in the number task was more gradual than in the color task. Discussion The findings suggest that the thresholds of subjective awareness in 5–6 year-olds and objective discrimination in 7–9 year-olds are similar to those in adults. Moreover, the emergent processes of subjective awareness and objective discrimination in 5–6 year-olds are also similar to those in adults. Our results support the level of processing hypothesis but suggest that its effects may differ across developmental stages.